Indian Mustard and Buckwheat as Trap Plants of Diamondback Moth (Plutella xylostella L.) in Cabbage Cultivation - Sapkota, B.; Regmi, R.; Thapa, R.B.; Tiwari, S. (Journal of Agriculture and Environment, 2022)
Diamondback moth (Plutella xylostella) is an important pest of crucifer crops. It greatly reduced both yield and crop quality on cabbage (Brassica oleracea var. capitata). The field study was conducted to evaluate the efficacy of two trap plants: Indian mustard (Brassica juncea), and Buckwheat (Fagopyrum esculentum) from November 2018 to March 2019 in Chitwan, Nepal. Diamondback moths’ population were similar in trap plants but was significantly lower as compared to the control plot. Diamondback moth larvae population was lower during early vegetative growth stages whereas trapping efficacy of trap crops were gradually reduced with the development of maturity in trap plants. The lowest damage of wrapper leaves were obtained in Indian mustard deployed trap plant followed by buckwheat trap plant and control respectively; however, the yield was similar in all treatments. In addition, natural enemies were observed higher in traps crops deployed plots compared to the control plots. Therefore, trap plants can be used as an alternative sustainable pest management tool to manage diamondback moth as well as increase the abundance of natural enemies.